Seminal Plasma Proteins Associated with The Fertility of Brahman Bulls in The Colombian Low Tropics - Liliana J. Chacón,; Germán D. Yepes,; Jaime Cardozo,; Fabian Rueda,; Viviana Castillo,; Andres Torres,; Jorge Martins,; Ariosto Ardila, (Tropical Life Sciences Research, 2023)
The sperm interacts with seminal plasma proteins during its transport through the female reproductive tract to reach the oocyte. Seminal plasma proteins have been associated as biomarkers of fertility in bovine males, while two-dimensional electrophoresis in polyacrylamide gels under denaturing conditions (2D-PAGE) is a useful technique for their separation, allowing their subsequent analysis with the aid of specialized software. Brahman bulls are known for their tolerance to tropical conditions such as low-quality pastures, high temperatures, and relative humidity as well as moderate resistance to infestations by parasites and insects. The present study describes the two-dimensional electrophoretic profiles of the seminal plasma proteins in the rainy and dry seasons, associating them with the fertility of Brahman bulls in the Colombian Orinoquía in a 90-days breeding season and a single-sire mating system (1 bull per 50 Brahman cows) with 60 consecutive days of rest. The fertility-related seminal plasma protein spots increased in the dry season. Likewise, a meaningful relationship was found between the protein spots that possibly coincide with the Binder of Sperm Proteins. It was also found that bulls with the highest percentages of pregnancy also had similarities in their 2D seminal plasma maps. We conclude that the seminal plasma protein profile of Brahman bulls raised in the Colombian low tropic changes between rainy and dry seasons, and such changes may influence the reproductive performance of those animals.